Automatic mapping of forest density from airborne LIDAR data - Trier, Øivind due (Geodesy and Cartography, 2015)
This paper presents new methods for the automatic mapping of vegetation from airborne lidar data. The methods are developed specifically for orienteering maps, which are detailed maps in scale 1:15,000 or 1:10,000 of forested areas. However, the methods may be modified to be used for automatic mapping of vegetation for national topographic map series in various scales, e.g., 1:25,000 or 1:50,000.We introduce the normalized difference vegetation density (NDVD) as an indicator of vegetation density in airborne lidar data. A modified version of NDVD is used for reduced runability mapping.By comparing pixel-by-pixel the automatic mapping with the manual survey in four different forest areas in Oslo, Norway, the correct classification rate varies from 71% to 75%. However, close investigation reveals that the automatic mapping is better than manual survey for open areas. On the other hand, the automatic mapping of reduced runability remains a difficult problem. In many cases, the automatic method is able to identify the major areas of reduced runability, while in other areas the correspondence is low between the automatic mapping and manual survey of reduced runability. Still, the automatic method may be used to quickly produce an initial mapping of reduced runability, or in the production of orienteering maps in remote areas where a full manual survey cannot be afforded.